(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The Automatic Room Comfort Controller was developed using a fuzzy logic–based control system to regulate indoor environmental conditions. The system uses three primary inputs—temperature, humidity, and occupancy—to generate two control outputs, namely Fan/AC speed and Window Position. The controller was designed and simulated using MATLAB’s Fuzzy Logic Designer, following defined membership functions and IF–THEN rule sets. Simulation results demonstrated that the fuzzy controller was able to adapt system responses according to varying room conditions, maintaining comfort while minimizing excessive energy use. The behavior observed across multiple input test scenarios showed that the system responded smoothly and consistently, avoiding abrupt switching common in traditional fixed threshold HVAC systems. Overall, the fuzzy logic model proved effective for real-time intelligent indoor climate regulation.